Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1972
DOI: 10.1159/000224646
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Differences between Normal Mouse Epidermis and Methylcholanthrene-Induced Squamous-Cell Carcinomas

Abstract: IgG preparations were made from antisera raised against the urea- and alkali-extracted antigens of normal mouse epidermis and methyl- cholanthrene-induced squamous-cell carcinomas. Immunodiffusion in agar with thoroughly adsorbed IgG immuno- globulins showed that the urea- and alkali-extracted proteins of the carcinomas had antigens in common. Antigens in common were also found in the epidermal urea-and alkali-extracted proteins, but the antigens common to the carcinoma proteins were not identical with the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

1973
1973
1979
1979

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The studies reported here on the urea proteins of epidermis, papilloma and carcinoma by fluorescence microscopy confirm the antigenic differences observed by immunodiffusion (Carruthers, 1970), and with the paired label technique (Bhattacharaya and Carruthers, 1972). The ureaextracted proteins of mammalian epidermis consist of several species as indicated by molecular sieve chromatography, and these components have a common antigenic determinant (Carruthers and Bhattacharaya, 1972a;Tezuku and Freedberg, 1972).…”
Section: Methodssupporting
confidence: 77%
See 4 more Smart Citations
“…The studies reported here on the urea proteins of epidermis, papilloma and carcinoma by fluorescence microscopy confirm the antigenic differences observed by immunodiffusion (Carruthers, 1970), and with the paired label technique (Bhattacharaya and Carruthers, 1972). The ureaextracted proteins of mammalian epidermis consist of several species as indicated by molecular sieve chromatography, and these components have a common antigenic determinant (Carruthers and Bhattacharaya, 1972a;Tezuku and Freedberg, 1972).…”
Section: Methodssupporting
confidence: 77%
“…The investigations of Rudall (1952) indicate that the fibrous or structural (urea-extracted) proteins of epidermis arise from the tonofilaments and are thus intracellularly derived. In this connection radiolabelled antibodies prepared against epidermal urea proteins did not penetrate epidermal cells in vivo (Bhattacharaya and Carruthers, 1972). Actually, Tezuka et al (1972) (Fig.…”
Section: Methodsmentioning
confidence: 78%
See 3 more Smart Citations